Growth, nodulation, yield, nitrogen uptake, and economics of lentil as influenced by sowing time, tillage, and management practices - Mukherjee, Bishal; Kumar Naskar, Manish; Nath, Rajib; Atta, Kousik; Visha Kumari, Venugopalan; Banerjee, Purabi; Alamri, Saud; Patra, Kiranmoy; Laing, Alison M.; Skalicky, Milan; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
A field experiment was carried out during the two consecutive Rabi seasons to ascertain the impact of sowing timing, tillage operation, and variety on the growth, development, yield characteristics, and as nitrogen uptake in lentils. Treatments were two different sowing conditions (S1: early sowing after har-vesting of short duration Kharif rice, S2: delayed sowing after harvesting of long duration Kharif rice), three different tillage operations (T1: Relay cropping, T2: Zero tillage, T3: Conventional tillage) and two different varieties (V1: short duration: L4717, V2: long period: Moitri). All treatments were arranged in a split-plot design and repeated 3 times. The results showed a significant influence of sowing time, tillage and variety on different parameters of lentils. Early November sown lentils yielded more than late November sown lentils. Adapting short-duration variety L4717 over the long-duration cultivar Moitri yield can increase by 5.9%. It provides higher yield and additional temporal space for incorporating current cash crops like leafy vegetables. Among the three tillage practices adopted, conventional tillage produced the lowest yield in both experimental years. In contrast, the yield increase was observed by 6.9% and 26.9 % in relay cropping and zero tillage sys-tems, respectively. Early sown lentils with zero tillage and short duration variety attain particular phenophase (life cycle - 96.2 and 98.7 days for lentils during both years) faster than other combina-tions. Total N uptake by lentil grain and stover followed a similar trend to lentil growth and yield attributes. The growth parameters and number of nodules/plant were highly correlated (nodules/plant at 45 DAS, LAI and plant height at 75 DAS and dry aerial biomass accumulation at harvest) with nitrogen uptake at different stages life cycle. Maximum gross return, net return and Benefit:Cost ratio under treatment combination early sowing + zero tillage + short duration variety in the experiment with the relative minimum cost of cultivation was also calculated for lentil cultivated in this zone. Therefore short, duration lentil cultivars, in combination with early sowing in the zero-tillage system, are the best agronomic approach for the sustainability of lentil production after monsoon rice.